Indicators’ behavior related to the patients care with spontaneous subarachnoid hemorrhage in the Cienfuegos province - Mercedes Soledad Corona Fonseca; Ada Sánchez Lozano; Ernesto Castro López; Luis Alberto Corona Martínez (Medisur)
Background: the spontaneous subarachnoid hemorrhage’s health importance, it’s recognized as a health problem. Objective: to determine the behavior of some indicators related to medical care for patients with spontaneous subarachnoid hemorrhage, in the provincial context. Methods: Observational, descriptive-correlational and retrospective study of 96 patients with spontaneous subarachnoid hemorrhage between 2016 and 2021. The behavior of selected indicators was analyzed in relation to various variables. In the statistical analysis, the Odds Ratio and its confidence interval were used as statisticians. Results: 22% of the patients were diagnosed after the first 48 hours after the onset of symptoms, while 13 patients (14%) required more than one assistance for diagnosis. The occurrence of late diagnosis when bleeding was not identified at the first visit was significant (OR 21.8[5.1;91.8]). Twelve patients were admitted outside of specialized units; this situation was observed more in patients under 60 years of age (21% vs 4%; OR 5.7[1.1;27.9]), and in whom the diagnosis was made 48 hours after the onset of manifestations (29% vs 8%; OR 4.6[1.3;16.2]). Of the 35 patients transferred to another institution for neurosurgical treatment, only four (12%) were evacuated in the first 72 hours. Conclusions: gaps are identified in the patients’ care with subarachnoid hemorrhage in the provincial context; The admission of patients outside specialized units and the late transfer to institutions with neurovascular surgery service stand out.